(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
Two species of the genus Nymphaea L. (N. alba L. and N. candida J. Presl & C. Presl) were first time recorded on the territory of the Nyzhnodniprovsky sands area. It grow in the center of the Kozachelagerska arena on the territory of the Radenske department of the national park "Oleshkivski Pisky". Administratively, it is the area of the Radensk village council of Oleshky district, Kherson region. Nymphaea alba and N. candida grow in two small lakes located close to each other. These lakes were formed as a result of filling the ground water into crater of the aircraft bombs (there was the military firing range before the creation of a national park in this area). Lakes of round shape, with overgrown shores. The Nymphaea candida and N. alba communities belong to the Nymphaeion albae Oberdorfer 1957, Potametalia W. Koch, Potametea Klika in Klika et Novak 1941, 1926. The growth of species of the Nymphaea species is possible in this area due to the close occurrence of groundwater. There is no doubt that species of the genus Nymphaea have recently appeared on the Kozachelagerska arena, since the lakes in which they occur are of the anthropogenic origin and were formed in the second half of the twentieth century as a result of the explosion of powerful aircraft bombs. Nymphaea species migrated there, in our opinion, naturally with the help of wetlands birds. The discovered locations there of N. candida and N. alba are of high sozological value. Although both species are quite common in the nearby plains of the Lower Dnieper, this is the first finding of the species of the genus Nymphaea in the territory of the Nizhnodniprovsky sands. The communities of Nymphaeeta candidae and Nymphaeeta albae are included in the Green Book of Ukraine. In addition, Nymphae alba belongs to regionally rare plants in the Kherson region. In order to further preserve them, we consider it necessary to continuously monitoring of their populations and, if necessary, introduce biotechnical measures for their conservation.